Effect of stressful life events on subclinical psychotic symptoms in first-degree relatives and healthy controls - Lachowicz, Aleksandra M.; Vaessen, Thomas; van Aubel, Evelyne; Butjosa, Anna; Reininghaus, Ulrich; Myin-Germeys, Inez (Schizophrenia research, 2022)
Exposure to Stressful Life Events (SLEs) has been linked to psychosis. However, the combined effect of SLEs and familial risk on subclinical psychotic symptoms over time remains unknown. The objective of the present study was to investigate the effect of SLEs on the level of subclinical psychotic symptoms in individuals with and without familial vulnerability for psychosis. Data were collected from siblings of individuals diagnosed with psychotic disorder and healthy controls at baseline (N = 293) and three years later at follow-up (N = 928). We assessed self-reported and observer-rated subclinical positive, negative, and depressive psychotic symptoms. Participants reported the number of SLEs in the preceding 6 months. A multilevel multivariate regression analysis revealed a positive association between the retrospectively assessed number of SLEs and symptom levels, regardless of vulnerability status (p < .001 for all outcomes). The prospective analysis demonstrated that exposure to SLEs at baseline predicted higher levels of subclinical psychotic symptoms at follow-up. However, after controlling for the level of symptoms at baseline, these associations were no longer significant. Again, the vulnerability status did not modify these results. Nevertheless, siblings in our sample were approximating the end of the critical period for the development of psychotic disorder (mean age at baseline M = 29 and follow-up M = 34). The findings partly support the vulnerability-stress model of psychosis, yet do not confirm the role of familial risk in this association. SLEs may represent a risk factor for psychosis at a population level, thus supporting the continuity of the psychosis spectrum in terms of associated risk factors.